Semisynthesis of Andrographolide Derivatives and Evaluation of Their Antitumour Properties - Rao, Jada Srinivasa (2004)
Previously, andrographolide, which is the major diterpenoid of Andrographis paniculata, was shown to have in vivo antitumour activity against human breast tumour xenografts. In this study, among the four compounds isolated from A. paniculata, andrographolide was the most potent compound with a mean ICso value of 8 IlM in MCF-7 human breast cancer cells. Neoandrographolide showed a weak cytotoxic effect, whereas 14-deoxy-ll, 12-didehydroandrographolide and 14-deoxyandrographolide failed to exhibit growth inhibitory effect at the highest tested concentration of 100 IlM. Owing to this, andrographolide was considered as the lead compound in the discovery of potent and selective antitumour agents. Using andrographolide isolated from A. paniculata as one of the starting materials, 3,19-